Viktor Mikhailovich Zhdanov and the eradication of smallpox - Popov, Valery Ivanovich; Capasso, Lorenzo; Naraeva, Natalya Yurievna (Medicina Historica, 2022)
Considering current epidemiological and social phenomena such as COVID-19 pandemic, re-occurrence of monkeypox and vaccine hesitancy, the authors chose to delineate an historical, human, and scientific profile of Dr. Viktor Mikhailovich Zhdanov, as a key figure related not only to smallpox eradication, but also to the building up of worldwide vaccination strategies. The authors present some of Zhdanov main life and scientific experiences and awards in virology, epidemiology, and public health. The authors highlight the need for international commitment to cooperate in the fields of vaccine research and vaccine hesitancy.